2009
DOI: 10.1007/s00038-009-8078-5
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the integration of HIV treatment and prevention: findings from a process evaluation of a community-based, national capacity-building intervention

Abstract: Study findings help distinguish a community-based concept of HIV-related integration from alternative uses of the term while pointing out key tensions associated with efforts to integrate HIV prevention and treatment in a community-based context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Integration has been raised as a priority in the context of limited resources for HIV/AIDS responses [ 35 , 36 , 51 ]. In economic theory, this model has the potential advantages on technical (focusing on unit cost of services) and allocative efficiency (focusing on cost-effectiveness of services) [ 52 ]. Recent studies confirmed that integrated HIV/AIDS service delivery was more efficient than stand-alone services [ 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integration has been raised as a priority in the context of limited resources for HIV/AIDS responses [ 35 , 36 , 51 ]. In economic theory, this model has the potential advantages on technical (focusing on unit cost of services) and allocative efficiency (focusing on cost-effectiveness of services) [ 52 ]. Recent studies confirmed that integrated HIV/AIDS service delivery was more efficient than stand-alone services [ 9 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is limited reliable data on immigrants' health status and the prevalence of infectious diseases within this population, they are considered particularly vulnerable to HIV infection (Del Amo et al 2004;Hamers et al 2006). Underutilization of HIV health services for prevention, testing and treatment has been identified as a factor that contributes to vulnerability (Chee et al 2005;Mykhalovskiy et al 2009;Shedlin and Shulman 2004). Knowledge on HIV testing among immigrants is limited and the available data suggests a wide variation across countries; nevertheless, they tend to present high rates of undiagnosed HIV infection and to utilize HIV health services at a later stage of disease (Burns et al 2007;Sinka et al 2003;Williamson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…10,14 The political grievances expressed in this study indicates weakness in interpretation of integration of CHW strategy in health systems. 37 Furthermore, it is suggested that CHWs program sustainability should not end up handing over program to Local Government without support in training, allowances and supervision of CHWs. 38 The lack of appropriate trainings in maternal health services on majority of CHWs in Bagamoyo and Mkuranga districts is an indication of the bigger picture characterizing the whole country and as well in other low-and-middle income countries about the value of CHWs and their contributing factor in the primary health system.…”
Section: Discussionmentioning
confidence: 99%